Pengaruh Komunikasi Interpersonal Guru Terhadap Peningkatan Minat Belajar Siswa Kelas VIII Pada Pembelajaran PAK di SMP YPK Ebenhaezer Sarmi - Mega Mustika Zega (Sekolah Tinggi Teologi Real Batam, 2020)
This research starts from a problem encountered by researchers in the field, where researchers find students at YPK Junior High School Ebenhaezer Sarmi lacking interest in learning. In learning students often experience boredom and passivity, so only teachers who look active. The application of interpersonal communication between teacher and students has not been maximized, so that it results in an atmosphere of learning even what is very visible is that teacher and student communication is very minimal. . Therefore, the authors formulate the problem, namely how the teacher's interpersonal communication, increase student learning interest, and how much influence the teacher's interpersonal communication on increasing student learning interest. To find the answer, the authors analyze the data using quantitative research and SPSS assistance, the authors conclude that the teacher's Interpersonal Communication has an influence on Student Learning Interest. The amount of influence that the author gets is 63%.